Exploring Emotion Recognition in Adults and Adolescents with Anorexia Nervosa Using a Body Motion Paradigm. (22nd March 2015) - Lang, Katie; Dapelo, Marcela Marin; Khondoker, Mizanur; Morris, Robin; Surguladze, Simon; Treasure, Janet; Tchanturia, Kate
Abstract Objective There is consistent evidence of difficulties in social cognition in adults with anorexia nervosa (AN), but less is known about adolescents. The aim of this study was to investigate the ability to recognise emotion expressed in body movement in adults and adolescents with AN. Method One hundred and ninety‐three females participated in the study (AN = 97: 61 adults and 36 adolescents). The performance of participants with AN on a body emotion recognition task was compared to age‐matched healthy controls (HC = 96). Results AN participants were significantly worse than HC recognising sadness, with adolescent AN participants showing worse performance overall. There were no difficulties in the recognition of other emotions. Discussion The results partially support previous studies and the literature on facial emotion recognition, showing poorer recognition of sadness in AN. The results also suggest that difficulties in emotion recognition through body movements may be more subtle than other socio‐emotional difficulties observed in AN. Copyright © 2015 John Wiley & Sons, Ltd and Eating Disorders Association.